Thyroid dysfunctions in adult patients after allogeneic hematopoietic stem cell transplantation. Issue 10 (29th August 2020) - Ataca Atilla, Pinar; Akkus, Erman; Atilla, Erden; Gokmen, Neslihan; Civriz Bozdag, Sinem; Kurt Yuksel, Meltem; Toprak, Selami Kocak; Baskal, Nilgun; Akan, Hamdi; Demirer, Taner; Topcuoglu, Pervin; Arslan, Onder; et al.
Abstract: Introduction: Thyroid dysfunction (TD) is one of the major endocrinopathies shown after allogeneic hematopoietic stem cell transplantation over the long term. The incidence and the risk factors for TD have varied widely. Patients and Methods: Two hundred and fifty‐nine patients with pre‐transplant normal thyroid function tests who survived at least 1 year after allo‐HSCT between 2006‐2016 were included in the study. Results: Sixty‐four patients (25%) developed TD at median of 34 months (range, 1‐112 months). Hypothyroidism was detected in 32 patients (12%): 5 patients had primary hypothyroidism, and subclinical hypothyroidism occurred in 27 patients. 18 patients (7%) were diagnosed with hyperthyroidism: 2 patients (0.07%) were treated for primary hyperthyroidism, and 16 patients (6%) were followed for subclinical hyperthyroidism. Euthyroid sick syndrome occurred in 14 cases. None of the patients with thyroid dysfunction developed secondary thyroid malignancy. Receiving high‐dose TBI ( P = .001) was found to be significant risk for hypothyroidism; older age than median ( P = .01) and pre‐transplant active disease ( P < .0001) were related to hyperthyroidism. Conclusions: Thyroid dysfunction, mostly hypothyroidism, is a long‐term complication after allo‐HSCT in 25% of patients. Older age, pre‐transplant active disease, and receiving TBI are among the risk factors. Sustained long‐term monitoring of thyroid function test should be considered post allo‐HSCT.